Preparation of β"-Al2O3 electrolytes by freeze-drying and SPS - Li, Kaiyun; Ma, Mingyuan; Yang, Yang; Liang, Sen; Zhang, Xiao (Ceramics international, 2021)
Na-ionic conductivity and mechanical strength are two important parameters for β"-Al2O3 ceramics used as electrolyte materials. In this study, the ice-templating and freeze-drying processes were used to prepare uniformly porous Al2O3 powder with a certain degree of crystallographic orientation. With the help of spark plasma sintering (SPS) process, solid samples were fabricated from the porous power at a low temperature (1100 °C). Finally, highly conductive and highly strong β"-Al2O3 electrolytes were prepared after the solid samples were subject to further treatment at a high temperature (1600 °C). The scanning electron microscopy (SEM) results indicate that integration of the initial SPS process and further high-temperature sintering treatment have turned the freeze-dried Al2O3 powder to β"-Al2O3 samples whose grain structure is similar to the “brick-bridge-mortar” structure. Regarding such β"-Al2O3 samples, the bending strength parallel to the pressure direction is up to 273 MPa; the degree of crystallographic orientation, 0.25, and the ionic conductivity perpendicular to the pressure direction, 0.239 S cm−1 at 350 °C. Therefore, it can be concluded that the combination of freeze-drying, SPS and an additional high-temperature sintering process has helped generate a structure that improves the ion mobility and bending strength of the β"-Al2O3 ceramic, and thereby improving its strength and ionic conductivity.